Industry 4.0 - shaping the future of the digital world : proceedings of the 2nd International Conference on Sustainable Smart Manufacturing (S2M 2019), 9-11 April 2019, Manchester, UK /: proceedings of the 2nd International Conference on Sustainable Smart Manufacturing (S2M 2019), 9-11 April 2019, Manchester, UK. (2020) - Unknown
No abstract available